HPLC-DAD-ESI-MS/MS analysis of fruits from Firmiana simplex (L.) and evaluation of their antioxidant and antigenotoxic properties - Ghareeb, Mosad Ahmed; Mohamed, Tamer; Sobeh, Mansour; Wink, Michael (Pharmacotherapy, 2018)
Objectives The secondary metabolites of the fruits of Firmiana simplex (L.) were analysed by LC-DAD-ESI-MS/MS; furthermore, we evaluated their antioxidant and antigenotoxic properties. Methods The antioxidant activity was investigated using the 2,2′-diphenyl-1-picrylhydrazyl radical (DPPH), the 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt (ABTS) and the ferric reducing antioxidant power (FRAP) assays. The antigenotoxic potential was determined via the comet assay. Key findings The ethyl acetate fraction (EtOAc) was analysed by LC-DAD-ESI-MS/MS: phenolic acids and flavonoids were the main polyphenols of the fruits. The EtOAc fraction yielded the highest content of polyphenols with 314.61 mg GAE/g extract, followed by 297.51, 153.75, 101.47, 97.19 for dichloromethane, butanol, methanol and water extracts, respectively. As expected, a strong correlation exists between the antioxidant activity of the investigated extracts and their total phenolic content. In the DPPH assay, the IC50 value of the most active EtOAc fraction was 6.79 μg/ml, relative to 2.92 μg/ml of the standard ascorbic acid. ABTS and FRAP assays supported the results of DPPH assay. Moreover, using the comet assay, we could show that the phenol-rich EtOAc extract exhibits an antigenotoxic potential in human liver cancer cells (Hep-G2) treated with hydrogen peroxide (H2O2) as a genotoxic agent. Conclusions The fruits of Firmiana simplex may be a good natural source of antioxidant and antigenotoxic agents.